A Gompertz model of the strategy inventory for language learning questionnaire - Johannah Jamalul Kiram; Jumat Sulaiman; Suyansah Swanto; Wardatul Akmam Din (Centre for Environment Social and Economic Research, 2014)
This study aims to construct a nonlinear mathematical model using a modified Gompertz model into a data with six independent variables and one dependent variable. The six independent variables represents the six language learning strategies and the dependent variable is the language proficiency of two hundred and thirty pre-university students of Universiti Malaysia Sabah. These language learning strategies are based upon a self-report questionnaire, called the Strategy inventory for Language Learning. These students then sat for the Malaysian University English Test. The Akaike information criterion of the model was calculated, and the model’s goodness-of-fit was tested.